Cooperative Learning Style Develops Social Skills in Mathematics of College Freshmen Students - Maria Emely Cristy Mayordomo (Philippine Association of Institutions for Research, Inc., 2014)
Most of the students isolate or compete themselves in learning mathematics, sitting alone and struggling in understanding the materials or solve the assigned problems (Davidson, 1990).  Cooperative learning in mathematics is an effective tool for meeting the individual needs of students. The relationship of students might have developed and shared common goals as they interact with each other. This study focuses on determining students' perception on the effects of cooperative learning style in enhancing the social skills of students. The researcher used descriptive-correlational design in gathering information and material evidence relating to cooperative learning and social skills of the students. Questionnaire was used and administered to 44 students of Tagum Doctors College, Inc. as the respondents of the study. The researcher uses the following statistical tools: mean, t-test, and Pearson Product - Moment Coefficient of Correlation. The result shows that cooperative learning enhances the social skills of the students. There was a high correlation between cooperative learning and social skills of the students. This study concludes that the more the students engaged in cooperative learning, the higher the level the students develop their social skills.